Wittgenstein's Account of Rule-Following and Its Implications - Langseth, Jonathan (Stance: an international undergraduate philosophy journal, 2019)
In this paper I present an interpretation of Wittgenstein’s account of rule-following, including what implications he suggests this account has for philosophy. The account suggests that neither one’s interpretation nor the rule itself are criteria by which we may conclude a rule was followed correctly or not. Rather it is through training, regularity, habit and social expectation-in short, by the consequences of action-that an action is considered in accord with a rule. I argue that even if we accept Wittgenstein’s account of rule-following, certain philosophically important implications follow.